Relationship between Symbiodiniaceae chlorophyll a concentration and cell density in scleractinian corals across regions, species, and health status - Ann Marie Hulver; Zoë Watson; Rowan H. McLachlan; Andréa G. Grottoli (Marine Biology, 2026)
Chlorophyll a is an essential photosynthetic pigment in the coral endosymbiotic algae (Symbiodiniaceae). In healthy corals there is often an exponential decay relationship between chlorophyll a per Symbiodiniaceae cell and Symbiodiniaceae cell density. However, few studies have explored the surface area normalized relationship of these two metrics. Here, we evaluated the strength and variability of these relationships between chlorophyll a concentration and Symbiodiniaceae cell density, chlorophyll a per Symbiodiniaceae cell and Symbiodiniaceae cell density, and how these relationships differ between regions, species, and coral health status. We performed regression analyses on 482 data points from 10 coral species originating from four regions. As expected overall, chlorophyll a increased as Symbiodiniaceae cell density increased and there was an exponential decay relationship between chlorophyll a per Symbiodiniaceae cell and Symbiodiniaceae cell density. However, the strength and statistical significance of these relationships varied, sometimes dramatically, among regions, species, and with coral health status. Thus, measurements of one of these variables is not always a good proxy for another, highlighting the importance of measuring both chlorophyll a and Symbiodiniaceae cell density when quantifying this aspect of coral physiology.